How far is America from Here? : Selected Proceedings of the First World Congress of the International American Studies Association, 22-24 May 2003 - Haen, Theo d' (Text (Rodopi (Firm)), 2005)
How Far is America From Here? approaches American nations and cultures from a comparative and interdisciplinary perspective. It is very much at the heart of this comparative agenda that "America" be considered as a hemispheric and global matter. It discusses American identities relationally, whether the relations under discussion operate within the borders of the United States, throughout the Americas, and/or worldwide. The various articles here gathered interrogate the very notion of "America": which, whose America, when, why now, how? What is meant by "far"-distance, discursive formations, i.